DEVELOPMENT OF TOURISM FACILITIES AND ITS IMPACT ON THE ECONOMIC VALUE OF WANUREJO TOURISM VILLAGE - Suwandojo, Dodik Prakoso Eko Hery; Rosalina Nur Annisa,; Rekta Deskarina, (Journal of Innovation Research and Knowledge, 2024)
Tourism Village is one of the tourist destinations that attracts tourists. The development of tourist facilities in tourist villages is important because it has an impact on the economic value of tourist villages, especially Wanurejo Tourism Village located in Borobudur District, Borobudur Temple area. The research method used is descriptive qualitative with data collection techniques of observation, interviews, and documentation. The results showed that the development of tourist facilities in Wanurejo Tourism Village has been carried out gradually and holistically, taking into account various aspects. The development of tourist facilities has had a positive impact on the economic value of tourist villages, including an increase in the number of tourist visits, an increase in tourist village income, and the creation of new jobs. This study provides an overview of the development of tourist facilities and its impact on the economic value of tourist villages. However, this study has not discussed the impact analysis of the development of tourist facilities on other aspects of Wanurejo Tourism Village, such as social and cultural.